Anti-cyclic citrullinated peptide antibodies are associated with radiographic damage but not disease activity in early rheumatoid arthritis diagnosed in 2006–2011. (1st November 2020) - Ziegelasch, M; Boman, A; Martinsson, K; Thyberg, I; Jacobs, C; Nyhäll-Wåhlin, BM; Svärd, A; Berglin, E; Rantapää-Dahlqvist, S; Skogh, T; Kastbom, A
Abstract : Objective: The discovery of anti-citrullinated protein antibodies (ACPAs) and the introduction of new therapeutic options have had profound impacts on early rheumatoid arthritis (RA) care. Since ACPA status, most widely assessed as reactivity to cyclic citrullinated peptides (CCPs), influences treatment decisions in early RA, we aimed to determine whether anti-CCP remains a predictor of disease activity and radiographic joint damage in more recent 'real-world' early RA. Method: Two observational early RA cohorts from Sweden enrolled patients in 1996–1999 (TIRA-1, n = 239) and 2006–2009 (TIRA-2, n = 444). Clinical and radiographic data and ongoing treatment were prospectively collected up to 3 years. Two other cohorts served as confirmation cohorts (TRAM-1, with enrolment 1996–2000, n = 249; and TRAM-2, 2006–2011, n = 528). Baseline anti-CCP status was related to disease activity, pharmacotherapy, and radiographic joint damage according to Larsen score. Results: In the TIRA-1 cohort, anti-CCP-positive patients had significantly higher 28-joint Disease Activity Score, swollen joint count, C-reactive protein level, and erythrocyte sedimentation rate during follow-up compared with anti-CCP-negative patients. In TIRA-2, no such differences were found, but baseline anti-CCP positivity was associated with higher 3 year Larsen score (5.4 vs 3.5, p = 0.039). In TRAM-2, anti-CCP also predicted radiographic damage (8.9 vs 6.7, p = 0.027), with no significant differences in disease activity. Conclusion: In the early RA cohorts recruiting patients in 2006–2011, baseline anti-CCP positivity was not associated with disease activity over time, but was associated with increased radiographic damage at follow-up. Hence, close radiographic monitoring is warranted in early anti-CCP-positive RA regardless of disease activity.